1998
DOI: 10.1046/j.1365-2893.1998.00084.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and characterization of the hepatitis G virus helicase

Abstract: The hepatitis G virus (HGV) is a new member of the Flaviviridae family and has a genomic organization similar to that of hepatitis C virus (HCV). Protein sequence motifs are present suggesting that HGV encodes a serine proteinase, an RNA‐dependent RNA polymerase and a helicase. We have cloned and expressed the putative helicase of HGV and have shown that it contains a poly (U)‐stimulated NTPase activity and is able to function as a DNA helicase. Preliminary characterization of the HGV helicase activity reveals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…On the basis of sequence motif analysis, the HGV NS3 protein is predictive of a multifunctional protein containing serine protease, ATPase, and RNA helicase activities (2,14). Recently, it was found that the HGV NS3 protein has the ATPase and DNA helicase activities (12). In this study we confirm that the HGV NS3 protein has an RNA-stimulated ATPase activity and an RNA helicase activity, and we characterize the biochemical properties of the protein in detail.…”
Section: Discussionsupporting
confidence: 68%
“…On the basis of sequence motif analysis, the HGV NS3 protein is predictive of a multifunctional protein containing serine protease, ATPase, and RNA helicase activities (2,14). Recently, it was found that the HGV NS3 protein has the ATPase and DNA helicase activities (12). In this study we confirm that the HGV NS3 protein has an RNA-stimulated ATPase activity and an RNA helicase activity, and we characterize the biochemical properties of the protein in detail.…”
Section: Discussionsupporting
confidence: 68%
“…To date, however, the RNA helicase activity of flavivirus was demonstrated only in the NS3 protein of dengue virus type 2 [4]. The RNA‐stimulated NTPase and RNA helicase activities were also identified in the NS3 proteins of viruses which are genetically related to flavivirus such as hepatitis C virus (HCV), hepatitis G virus (HGV) and bovine viral diarrhea virus, a pestivirus (BVDV) [10–19]. The roles of such enzymatic activities of the flavivirus NS3 protein in viral replication are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitors of the helicase of Herpes simplex virus have been identified (208). The HCV (69,189) and HGV (134), helicases have been cloned, expressed, and characterized. The helicase of the Flaviviridae belongs to the DEAD (Asp-Glu-Ala-Asp) box family of RNA helicases (115).…”
Section: Inhibition Of Helicasementioning
confidence: 99%